2014
DOI: 10.1111/bcp.12251
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and their relevance to ABC transporters

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs, which regulate the expression of their target genes post-transcriptionally by RNA interference. They are involved in almost all cellular processes, including proliferation, differentiation, apoptosis, cell survival and the maintenance of tissue specificity. Recent findings also suggest that efflux pumps of the ABC (ATP-binding cassette) transporter family are subject to miRNA-mediated gene regulation. Moreover, it seems that ABC transporters are embedded in a concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 66 publications
0
52
0
2
Order By: Relevance
“…To evaluate the expression of selected miRNAs in preterm placentas with chorioaminionitis, we performed qPCR analysis of miRNAs selected on the basis of their regulatory actions on P-gp ( miR-145, miR-200c, miR-331-5p and miR-451 ) [44]. Placental expression of miR-331-5p (p=0.003) was significantly increased in the PTDC compared to the PTD group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the expression of selected miRNAs in preterm placentas with chorioaminionitis, we performed qPCR analysis of miRNAs selected on the basis of their regulatory actions on P-gp ( miR-145, miR-200c, miR-331-5p and miR-451 ) [44]. Placental expression of miR-331-5p (p=0.003) was significantly increased in the PTDC compared to the PTD group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Often, these studies demonstrated that BCRP/ABCG2 expression is altered as consequence of treatment with certain drugs, e.g., by inducing a reduction of ABCG2 promoter DNA methylation 45 or altering miRNA expression (reviewed in Haenisch et al 46 ). Often, these studies demonstrated that BCRP/ABCG2 expression is altered as consequence of treatment with certain drugs, e.g., by inducing a reduction of ABCG2 promoter DNA methylation 45 or altering miRNA expression (reviewed in Haenisch et al 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over 329 target genes of let‐7a‐5p have been identified in low‐throughput or high‐throughput miRNA targeting studies from the MiRTarBase miRNA Targets data set, but did not include ABCC2 . ABCC5 and ABCC10 are apparent targets but the localization and function of these transporters are not well understood in liver . Because a gene can be regulated by many different miRNAs depending on the cellular context, it is not surprising that ABCC2 expression in HepG2 cells and in human peripheral blood monocytic cells is regulated by miRNA‐379 .…”
Section: Discussionmentioning
confidence: 99%